SYNTHESIS AND EVALUATION OF ANTIMICROBIAL POTENTIAL OF CUO NANOPARTICLES - K. P. BHOKARE; S. S. SHENDE; N. S. PANDHARE; N. D. GAIKWAD; K. A. CHORMULE (The Bioscan, 2018)
Low temperature chemical synthesis of copper oxide nanoparticles (CuO) was achieved in aqueous solution using L-Ascorbic acid as a reductant and the cationic surfactant Cetyltrimethyl ammonium bromide (CTAB) as a capping agent to assessed their antimicrobial potential against phytopathogens.CuO nanoparticles shown antibacterial activity against all the tested bacterial cultures viz., Escherichia coli (12.87±1.80), Proteus sp. (12.5±2.39), Pseudomonas aeruginosa (7.3±1.92), Staphylococcus (23.87±2.1), Xanthomonas axonopodis pv. punicae (21.7± 2.65); similarly antifungal activity against fungal cultures viz., Aspergillus niger (15.62±1.06), Alternaria sesami (22.25±2.31), Colletotrichum lindemunthianum (11.6±1.92), Fusarium udum (17.5±2.20). The maximum activity of CuO nanoparticles was found against Streptococcus aureus (23.875±2.1) while the minimum activity was found against Pseudomonas aeruginosa (7.3 ±1.92). Copper sulphate, L-Ascorbic acid did not shown any antimicrobial activity where as CTAB shown relatively less activity as compared to CuO nanopaticles. The synthesized cupper nanoparticles will presumably useful in formulation of various biopesticides and ecologically feasible effective management strategy against harmful pathogenic microorganism.